Safety and Tolerability of Topical Ophthalmic Triamcinolone Acetonide-Loaded Liposomes Formulation and Evaluation of Its Biologic Activity in Patients with Diabetic Macular Edema - Jose Navarro-Partida; Juan Carlos Altamirano-Vallejo; Alejandro Gonzalez-De la Rosa; Juan Armendariz-Borunda; Carlos Rodrigo Castro-Castaneda; Arturo Santos (MDPI AG, 2021)
Intravitreal injections (IVTs) of corticosteroids as triamcinolone acetonide (TA) are frequently used for the treatment of many vitreous and retinal disorders. However, IVTs are related to severe ocular complications. Lately, a topical ophthalmic TA-loaded liposomes formulation (TALF) was designed to transport TA into the posterior segment of the eye when instilled on the ocular surface. To evaluate the safety, tolerability, and biological activity of TALF, an animal study and a phase I clinical assay were performed. Moreover, four patients with diabetic macular edema (DME) were treated with TALF in order to explore the biological activity of the formulation. No inflammation, lens opacity, swelling, or increase in intraocular pressure were recorded after the instillation of TALF in any of the animal or clinical studies. Mainly, mild and transient adverse events such as dry eye and burning were reported. TALF significantly improves visual acuity and diminishes central foveal thickness in patients with DME. The current data demonstrate the safety, tolerability, and biological activity of TALF. It seems that TALF can be used topically to treat vitreous and retinal diseases that respond to TA such as DME, avoiding the use of corticosteroid IVTs and their associated hazards.